Assessment of the seismic behavior of self-centering eccentrically braced frames with vertical link-beam. (February 2023) - Rofooei, Fayaz R.; Soleimani, Mona
Abstract: Conventional eccentric braced frames often sustain large residual deformations and significant damages after strong earthquakes which may lead to heavy damages or even destruction of the structure. This paper proposes a self-centering, Y-inverted, eccentrically braced frame (SC-YEBF) which combines the lateral load resisting benefits of YEBF including strength, stiffness and energy dissipation capacity with the re-centering capacity of post-tensioned (PT) high strength steel strands used at beam-to-column connections. A design procedure is presented assuming that all the seismic input energy is dissipated through inherent damping and plastic deformations of the link-beams. Thus, in the presented design procedure, only the link-beams yield under the design earthquake and any other structural failure is prevented under the maximum considered earthquake (MCE). The feasibility of the proposed idea is checked first by cyclic loading analysis of a one-bay, one-story, SC-YEBF system using finite element models. Then, a simplified numerical approach for modeling such a system is presented. A series of nonlinear dynamic analyses are performed for a four-story steel frame equipped with SC-YEBF system under seven ground motions recorded on site classes C and D according to ASCE 7-16. The results indicate that the proposed system achieves the desired performance goals and sustains very small residual displacements. Also, the post-earthquake structural damage of main members including floor-beams, columns, and braces remains negligible.